Funding of geological exploration during transformation of the Russian economic system - S. M. Salmanov; Z. M. Nazarova; Yu. A. Leonidova (Известия высших учебных заведений: Геология и разведка, 2023)
Background. The mineral resource base is a strategic component of Russia’s economic security, being a critically important tool for strengthening the country’s position in the international arena. At the same time, economic shocks and geopolitical tensions negatively affect the investment attractiveness of geological exploration projects, which are highly important for the continuous reproduction of the country’s mineral resource base.Aim. Consideration of funding possibilities for geological exploration activities in Russia.Objectives. 1) To analyze the structure and state of geological exploration funding in Russia over the past five years; 2) to study the prospects and possibilities of attracting investments for different geological exploration stages in Russia; 3) to offer new methods and tools for optimizing the funding of geological exploration activities under the conditions of transformation of the Russian economic system.Materials and methods. The research materials included domestic and foreign scientific publications; reports and publications of the Federation Council Committee on Agriculture and Food Policy and Environmental Management of the Russian Federation, the Ministry of Natural Resources and Environment of the Russian Federation, the Federal Subsoil Resources Management Agency; the results of the “Geology, Revival of a Legend” initiative; McKinsey and OECD Global Forum on International Investment analytical materials. The materials were analyzed using a set of general and specialized scientific methods. Among them are statistical modeling and forecasting to assess the state and prospects of geological exploration funding in Russia; comparative analysis and synthesis, induction and deduction to study international experience in attracting alternative investments for geological research.Results. Proposals concerning the possibility of attracting additional funding at various stages of geological exploration through the creation of direct investment trust funds are formulated. Attention is also paid to such methods as streaming and acquisition of a fixed interest rate from production in exchange for an advance payment, which can be applied at later stages of exploration.Conclusion. New approaches and best international practices should be used to attract funding for various stages of geological exploration activities in Russia. This will make it possible to attract non-governmental resources, diversify methods of financial support, as well as to increase the investment attractiveness of geological exploration projects.